Evaluation of Buccoadhesive Propranolol Hydrochloride Formulations Containing Plantago psyllium Seed Mucilage and Carbopol 934P: Evaluation of buccoadhesive propranolol hydrochloride tablets - Majid Saeedi,; Jafar Akbari,; Ali Azarashk,; Katayoun Morteza-Semnani, (Iranian Journal of Pharmaceutical Sciences, 2014)
https://doi.org/10.22034/IJPS.2014.15250 Drug delivery via buccal mucosa by means of buccoadhesive formulations offer distinct advantages over peroral administration. Recently, plant gums and exudates have been screened for their use as pharmaceutical adjuvants. The aim of this study is to evaluate matrix tablets containing Plantago psyllium seed mucilage in addition to carbopol as a mucoadhesive agent, and propranolol hydrochloride as a model drug. Mucoadhesive tablets of propranolol were prepared using Plantago psyllium mucilage and Carbopol 934P. The swelling, erosion, mucoadhesion force, in vitro drug release were studied. Interaction between drug and polymers were investigated by DSC thermograms and FT-IR spectroscopy. The bioadhesion strength of formulations containing mucilage and carbopol was more than that of the tablets containing mucilage alone. The results also showed that bioadhesive strength increased with increase in the amount and viscosity of polymers. As the amount of mucilage increased from 6.25% per tablet (F1) to 43.75% (F7) drug release was increased. Combination of Plantago psyllium mucilage and Carbopol 934P modified the release rate and kinetic. The kinetic of drug release has changed by increase in amount of mucilage in these formulations. DSC and FT-IR studies showed no interaction between drug and formulations macromolecules. The use of Plantago psyllium mucilage and carbopol can optimize the drug release in propranolol HCl buccoadhesive tablets.